Two new species of ghost shrimp assigned to the genus Cheramus Spence Bate, 1888 (Crustacea: Decapoda: Axiidea: Callianassidae) from the Ryukyu Islands, Japan - Komai, Tomoyuki; Maenosono, Tadafumi; Fujita, Yoshihisa (Zootaxa, 2014)
Two new species of the callianassid ghost shrimp are described and illustrated on the basis of specimens from the Ryukyu Islands, Japan. These are provisionally assigned to the genus Cheramus Spence Bate, 1888, and appear closest to Callianassa acutirostella Sakai, 1988, also provisionally transferred to Cheramus herewith. These three species can be differentiated by characters of the telson, third maxilliped, chelipeds and uropod. The taxonomic status of Cheramus is briefly discussed.